Characterization of Sorbus aria-mediated silver nanoparticles and evaluation of antibacterial activity against Staphylococcus epidermidis clinical strains - N. O. Khromykh; O. O. Didur; T. V. Sklyar; L. Procházková; L. Nedbalová; J. Nebesarova; O. K. Balalaiev; N. V. Kuragina (Regulatory Mechanisms in Biosystems, 2025)
Biosynthesis of silver nanoparticles (AgNPs) using plant extracts serves as an attractive environmentally friendly and cost-effective alternative to the traditional methods of producing nanomaterials with antimicrobial properties. This article characterizes AgNPs derived from an aqueous leaf extract of Sorbus aria plants (Sa-AgNPs), and presents the results of their testing against antibiotic-resistant clinical bacterial strains. The formation of silver nanoparticles was observed visually according to the change in the color of solution and was confirmed by the induced plasmon resonance peak , recorded by UV-Vis spectroscopy at 450 nm. According to the TEM imaging, the biosynth esized Sa-AgNPs were spherical , with an average size of 47.5 nm , and exhibited a moderate polydispersity , with the PDI calculated as 0.138. The SEM images confirmed the spherical shape of the Sa-AgNPs and the absence of their agglomeration . The p hytochemicals from the plant matrix that served as reducing, stabilizing , and capping agents for Sa-AgNPs biosynthesis were identified using Fourier transform infrared spectroscopy as phenolics, alcohols, terpenes, and proteins, with hydroxyl, carbonyl, carboxyl, and amines being the responsible functional groups. The antibacterial activity of the biosynthesized silver nanoparticles was examined using the disc diffusion method against two clinically isolated Staphylococcus epidermidis strains that differed in sensitivity to some antibiotics from several classes. The growth inhibition of both S. epidermidis strains by Sa-AgNPs was dose-dependent at a concentration range of 15.625–1 , 000 µg / mL. The S . epidermidis strain that displayed a stronger resistan ce to several fluoroquinolones, cephalosp o rines and aminoglycosides, showed higher susceptibility to the antibacterial action of Sa-AgNPs than the less drug-resistant strain. The hemolytic assay revealed a good biological compatibility of the biosynthesized Sa-AgNPs at concentrations of up to 25 μg / mL. The study results confirmed the potential ability of phytosynthesized silver nanoparticles to achieve considerable success in the fight aga inst antibiotic resistance of S . epidermidis . Further research is needed to test a large number of resistant clinical strains to clarify the suitability of Sa-AgNPs for development of new antibacterial drugs.